2020
DOI: 10.1016/j.nedt.2020.104475
|View full text |Cite
|
Sign up to set email alerts
|

Global assessment instrument for quality of nursing doctoral education with a research focus: Validity and reliability study

Abstract: 23 Objectives: This study was designed to assess the content and construct validity and reliability 4 of the Quality of Nursing Doctoral Education (QNDE) instrument for nursing doctoral programmes with a research focus. Design:A cross-sectional, survey study.Settings: Using Qualtrics survey, the research team sent emails to potential participants providing a link to the study and the QNDE instrument.Participants: A total of 234 faculty and doctoral students participated: 17 faculty from 14 countries in the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
(28 reference statements)
0
19
0
Order By: Relevance
“…Following and monitoring the process of PhD education in Nursing has therefore been a topic on the agenda in the entire world 4,[11][12] . Increasingly complex and systematic assessment systems play a fundamental role in reorienting the training processes, and new indicators are needed to address this complexity, such as those herein discussed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following and monitoring the process of PhD education in Nursing has therefore been a topic on the agenda in the entire world 4,[11][12] . Increasingly complex and systematic assessment systems play a fundamental role in reorienting the training processes, and new indicators are needed to address this complexity, such as those herein discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Like the economic impact, the political impact lacks greater visibility. The global recognition of academic nurses for the quality of their PhD training in Nursing and the continuous assessment of the quality of the existing programs are imperious for the advancement of the profession, for the promotion of good Nursing practices, for the increase of associative leaderships and institutional management positions in the health system and academic training, and for the formulation and implementation of public policies and generation of processes and products 1,4,9,11,[18][19][20] . By directing towards solidarity strategies, a study carried out with Master's degree graduates from Angola and Mozambique, showed that they began to hold high positions such as managers, directors and State secretaries, in addition to working as managers in health and teaching programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The items which is evaluated by reliability test are only items that have been valid. Kim et al (2020) also used Alpha Cronbach to evaluate the quality of nursing doctoral education by validity and reliability tests.…”
Section: Information Stagementioning
confidence: 99%
“…most experts opinion about an asked question point in the same direction), which is most commonly measured through a content validity index (CVI) (Polit et al, 2007;Wan Ahmad et al, 2020). Each item validity was assessed through a five-point Likert scale (a slight variation from Kim et al (2020) and Polit et al (2007) which proposed a four-point scale), and relevant items were considered with a value of 4 or 5 (relevant and highly relevant) to make for a more restrictive validity criteria. Table 20 represent the I-CVI (item content validity index) and S-CVI (scale content validity index), which is computed using the average of I-CVI, instead of the universal agreement method which is more restrictive and therefore more likely to produce divergent results when evaluating new instruments (Polit et al, 2007).…”
Section: Experts' Assessmentmentioning
confidence: 99%